ELATIHAN CARA PENYIAPAN MAKANAN YANG SEHAT DAN AMAN: TEKNIK KOMPLEMENTER MEMANF AATKAN BAHAN MAKANAN LOKAL BAGI PENGELOLA TPA - Yuliati, Yuliati -; Rahayu, Tutiek (Universitas Negeri Yogyakarta, 2003)
This public service program aims to provide some knowledge and skill improvement on selecting and preparing children foods using complementary technique, and some knowledge improvement on composing children food menu. It is expected that after this program the participants will be able to design models and menu lists of children food menu using complementary technigue for nutritious substance especially protein. Although the food price is reduced, the nutritious content is better. Moreover, the children cared are protected from food poisoning, malnutrition and improve the awareness of selecting healthy foods in children as early as possible.The method applied in this program was lecture, discussion and practical work simulation. The presentation of the group practical work was in the form of a competition. The duration of this program was 33 hours. Participants were delegated from10 children involving 19 representatives.The program was conducted from 20 June to 12November 2002.The results show that most of the participants comment that this training is very useful in improving cooking activity in childeares.It is found that the competition model motivates the participants to actively attend the program. The evaluation thus shows that 84,3% of the participants achieve good result while the rest ( 15,7%) are in the average. Generally, the participants ( 77,7% ), before the training did not know the concepts of preparing healthy and safe foods.In order to improve protein nutritious value of food, participantas, presented 24 main dishes ( 8 lauk and 16 sayur ) composed in menu lists for 30 days using complementary technique. Key words: Complementary technique.